Evidence base of three comprehensive case studies following a common template - Scheuerle, Thomas; Schimpf, Gudrun-Christine; Mildenberger, Georg; Glänzel, Gunnar (CrESSI working papers, 2018)
Comprehensive Case Studies 1 and 3 of: Deliverable 2.1: Evidence base of three comprehensive case studies following a common template.
Gesehen am 10.02.2020